Shengqiyichang decoction regulates antitumor immunity in colorectal cancer by downregulating lymphocyte antigen 6 family member G6D via the protein kinase B/p38 mitogen-activated protein kinase signaling pathway - Run Xing Luo; Huai Liang Li; Yu Xiang Jia; Meng Gao; Zhao Yang Gao; Yi Ji; Shan Deng; Jie Ge Huo; Jian Zhang; Dong Jian Zhang (Heliyon)
The traditional Chinese medicine (TCM) formulation Shengqiyichang Decoction (SQYCD) has been reported to stimulate host immunity, and it has been administered for the treatment of colorectal cancer (CRC). Here, we applied network and bioinformatics analyses to elucidate the mechanisms by which SQYCD ameliorates CRC and validated its modes of action via in vivo and in vitro experiments. We identified 46 active compounds in SQYCD and selected 237 proteins as potential therapeutic targets in CRC, most notably p38 mitogen-activated protein kinase (p38⍺). Bioinformatics analyses demonstrated differential expression in CRC tissues and prognostic value of the genes encoding TNFα, MAPK14, CASP-3, MAPK1, AKT1, PRKACA, VEGF, IL-6, EGFR and ESR1. We then plotted receiver operating curves (ROC) and time-ROC for the differentially expressed genes (DEGs) ESR1 and AKT1 to predict the progress of CRC. We speculated that the AKT/p38α-MAPK signaling pathway is associated with the clinical prognosis of CRC. In a mouse model, we found that SQYCD inhibits CRC tumor growth by increasing CD4+ and CD8+ T cell abundance and decreasing the ratio of T-regulatory cells (Tregs) in the tumor microenvironment. In cultured mouse CRC cells, SQYCD selectively upregulated levels of the CRC-associated protein lymphocyte antigen 6 family member G6D, while the AKT activator SC-79 reversed this effect. The discoveries made herein suggest that SQYCD exerts a therapeutic effect in CRC by inhibiting Treg recruitment via inhibition of the AKT/p38α/LY6G6D signaling axis.